RESTful Web Services Development with a Model-Driven Engineering Approach - Gonçalves, Rafael Corveira da Cruz (2018)
A RESTful web service implementation requires following the constrains inherent to Representational State Transfer (REST) architectural style, which, being a non-trivial task, often leads to solutions that do not fulfill those requirements properly. Model-driven techniques have been proposed to improve the development of complex applications. In model-driven software development, software is not implemented manually based on informal descriptions, but partial or completely generated from formal models derived from metamodels. A model driven approach, materialized in a domain specific language that integrates the OpenAPI specification, an emerging standard for describing REST services, allows developers to use a design first approach in the web service development process, focusing in the definition of resources and their relationships, leaving the repetitive code production process to the automation provided by model-driven engineering techniques. This also allows to shift the creative coding process to the resolution of the complex business rules, instead of the tiresome and error-prone create, read, update, and delete operations. The code generation process covers the web service flow, from the establishment and exposure of the endpoints to the definition of database tables.